Origin of Ultrapotassic, Ultracalcic, Ultrabasic SiO2‐Undersaturated Magmas: The Case Study of the Pleistocene Cupaello Kamafugite Monogenetic Volcano, Central Italy - Michele Lustrino; Lorenzo Pistocchi; Sara Ronca; Francesca Innocenzi; Samuele Agostini (Geochemistry, Geophysics, Geosystems)
Abstract The Pleistocene (∼0.6 Ma) Cupaello monogenetic volcano, cropping out in central Italy, belongs to the Intra Apennine Province (IAP). It is represented by a single lava flow with kamafugitic composition, associated with a volumetrically limited pyroclastic deposit and a phosphate‐rich layer close to the small vent. This kamafugite is characterized by ultrapotassic (K2O = 5.2–7.6 mass %; K2O/Na2O = 18.0–33.9), ultracalcic (CaO/Al2O3 = 2.2–2.4), ultrabasic (SiO2 = 42.6–44.1 mass %), and SiO2‐undersaturated (∼29% CIPW normative leucite) composition, with a peculiar paragenesis (kalsilite, melilite, phlogopite, clinopyroxene, calcite, olivine and glass, plus accessory phases). Trace elements (e.g., high LILE, high LILE/HFSE, negative anomalies for Nb, Ta, Ti and Eu, and Pb peaks in primitive mantle‐normalized diagrams) and isotopic constraints (e.g., strongly radiogenic 87Sr/86Sr, unradiogenic 143Nd/144Nd, high Δ7/4) point to subduction‐modified mantle sources. Cupaello products fall within the field of the IAP volcanic products, which define, as a whole, clear negative correlations of compatible and incompatible trace elements, as well as of all the other major oxides, with CaO. These trends are here interpreted as the effect of assimilation of crustal carbonates rather than the presence of a Ca‐carbonatitic component in the source, as instead commonly reported in literature. Despite this general trend, we emphasize that Cupaello rocks derive from partial melting of a subduction‐modified carbonated phlogopite‐peridotite source, followed by a prolonged fractional crystallization of olivine‐ and melilite‐rich kalsilitolite assemblages. A carbonatitic component is required to explain the absence of feldspars in the ultrabasic, ultracalcic and strongly SiO2‐undersaturated magma, whose composition was possibly modified in minimal amounts by carbonate assimilation at shallow depths.